From strategic human resources to organization performance - Oliveira, Ana Rita Damas; Henriques, Paulo Alexandre Guedes Lopes; Oliveira, Teresa Cristina Clímaco Monteiro de (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Much has been written about the link between HR and performance, however consensus has yet not been found concerning the understanding on how that relationship comes together. Empirically, no direct impact has been found and research has only suggested an indirect impact. Consequently, the Strategic HRM field is particularly interested on the understanding of the mediating variables that impact the organization performance. Besides the integrated and business strategy alignment of the HR function, it should be considered that it is the people (HR) of the organization and not their practices that determine the company´s competitive advantage. (Messersmith & Guthrie, 2010) argue that it is the impact of those practices that represent “the true resource and enable a sustainable advantage over industry rivals”. The objetive of this research proposal is to study the impact of strategic human resources practices on the organization performance through a case study methodology, supported by longitudinal data. Namely, the project aims to achieve a deeper understanding of the variables that affect the process stream during strategy implementation. How the HR practices impact on people? And why human resources are the most valuable asset? These core premises are in line with the most recent economic concerns about people productivity, employment policies and labor flexibility.